Contraception Methods Selection Behavior Among Female Contraception Users - Lasiah Susanti; Wafiq Anikoh (Universitas Ahmad Dahlan, 2022)
Background: Family Planning aims to regulate childbirth and pregnancy interval by using various contraception methods. Eventhough there is many choice among contraception methods, intramuscular injection is still the most used method. This phenomena happened in Indonesia, nationally and locally in Pekanbaru. The behavior of female users in choosing contraception methods is based on their knowledge and attitude about contraception methods. Objective: This study purpose is to describe female conctraception users behavior in the selection of contraception methods in Pekanbaru city. Methods: Research conducted with descriptive observational study design. Sample size is 400, sample was taken by stratified random sampling technique at 12 primary health centers in the city of Pekanbaru. Results: Results: Results show majority respondents had improper contraception methods selection behavior . Majority respondent is in 30- 39 years age group, with educational attainment high school, and most of them is housewives. Conclusions: Majority female contraception users in Pekanbaru had improper contraception methods selection behavior